Management of Public Expenditure in the State of Gujarat: An Analysis - Agrawal, Sangita; Nayak, Dinkar (Indian Journal of Finance, 2013)
Allocation of expenditure at the state government level assumes significance since the major expenditure responsibilities are entrusted to them. The State Governments of India have been taking stringent measures to control the mounting expenditure. However, nothing substantial has been achieved because a large part of the expenditure is of revenue nature, which is beyond its control. It is in this context that this paper attempts to analyze the expenditure pattern of Gujarat State Government and its major issues, both qualitatively and quantitatively, which is affecting the state’s finances.